A Rare Pathogen in Acute Appendicitis: Two Cases with Comamonas testosteroni Infection and Literature Review - Tartar, Ayse Sagmak; Tartar, Tugay (Georg Thieme Verlag Kg, 2020)
Comamonas testosteroni (formerly Pseudomonas testosteroni ) is a common environmental bacterium, which is not a part of the human microbiome. It is rarely found as an infectious agent in clinical practice. The bacterium has low virulence potency and rarely causes human disease. Although this agent is generally considered to be of low virulence, reports of infections with C. testosteroni are increasing. With the exception of intra-abdominal infections, C. testosteroni is mainly reported as an opportunistic pathogen in immunocompromised patients. However, C. testosteroni has also been reported as a pathogen in patients with appendicitis (especially when perforated), suggesting that this bacterium may belong to the normal intestinal microbiota of some individuals. In this article, we present two children with appendicitis in whom C. testosteroni was isolated from appendix tissue samples.
Keywords: Comamonas; testosteroni; pediatric; infectious; acute appendicitis